The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4319/lo.2012.57.4.0945
|View full text |Cite
|
Sign up to set email alerts
|

Resuspension by fish facilitates the transport and redistribution of coastal sediments

Abstract: Oxygen availability restricts groundfish to the oxygenated, shallow margins of Saanich Inlet, an intermittently anoxic fjord in British Columbia, Canada. New and previously reported 210 Pb measurements in sediment cores compared with flux data from sediment traps indicate major focusing of sediments from the oxygenated margins to the anoxic basin seafloor. We present environmental and experimental evidence that groundfish activity in the margins is the major contributor to this focusing. Fine particles resusp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…() reported that over 75% of slender sole stomachs in Strait of Georgia had small crustaceans such as copepods. We often saw slender sole darting off bottom, especially in swarms of migrating plankton; these movements resuspended sediments to the point of creating dense turbidity layers near bottom in severe (<0.5 ml l −1 ) hypoxia (Katz et al ., ; Yahel et al ., ). Hypoxia intensity on the Saanich margins changes over the year, and mobile animals show strong responses as zooplankton adjust the depth of their diurnal migration (Sato et al ., ) while epibenthic animals move up and down slope (Chu & Tunnicliffe, ).…”
Section: Discussionmentioning
confidence: 98%
“…() reported that over 75% of slender sole stomachs in Strait of Georgia had small crustaceans such as copepods. We often saw slender sole darting off bottom, especially in swarms of migrating plankton; these movements resuspended sediments to the point of creating dense turbidity layers near bottom in severe (<0.5 ml l −1 ) hypoxia (Katz et al ., ; Yahel et al ., ). Hypoxia intensity on the Saanich margins changes over the year, and mobile animals show strong responses as zooplankton adjust the depth of their diurnal migration (Sato et al ., ) while epibenthic animals move up and down slope (Chu & Tunnicliffe, ).…”
Section: Discussionmentioning
confidence: 98%
“…() and Katz et al . () but with an extension into shallower depths (~45 m). This transect was repeated once every year until 2012, and in 2013, it was repeated three times at different times of the hypoxia cycle: after spring renewal (May), after a full summer of deoxygenation (September), and during the onset of oxygen recovery in the fall (October).…”
Section: Methodsmentioning
confidence: 99%
“…1b, Table S1) using remotely operated vehicles (ROV). This transect (~3 km length) begins in the middle of the inlet (~190 m depth) and is based on the one described in Yahel et al (2008) and Katz et al (2012) but with an extension into shallower depths (~45 m). This transect was repeated once every year until 2012, and in 2013, it was repeated three times at different times of the hypoxia cycle: after spring renewal (May), after a full summer of deoxygenation (September), and during the onset of oxygen recovery in the fall (October).…”
Section: Benthic Rov Transectsmentioning
confidence: 99%
“…Although slender sole is not a commercially valuable species (due to their small size), they resuspend large amounts of bottom sediments, which contribute to substantial fluxes in nutrient recycling and transport (Yahel et al 2008;Katz et al 2009Katz et al , 2012. High abundance and fidelity to low [O 2 ] env (Chu and Tunnicliffe 2015a) also suggest that they could be an important indicator species of hypoxic waters within their habitat range.…”
Section: Species-specific Traits Drive Community Responsementioning
confidence: 99%